Disparities between IgG4-related kidney disease and extrarenal IgG4-related disease in a case–control study based on 450 patients - Qiaozhu Zeng (Nature Portfolio, 2021)
Abstract We aimed to compare the demographic, clinical and laboratory characteristics between IgG4-related kidney disease (IgG4-RKD+) and extrarenal IgG4-related disease (IgG4-RKD−) in a large Chinese cohort, as well as describing the radiological and pathological features of IgG4-RKD+. We retrospectively analyzed the medical records of 470 IgG4-related disease (IgG4-RD) patients at Peking University People’s Hospital from January 2004 to January 2020. The demographic, clinical, laboratory, radiological and pathological characteristics between IgG4-RKD+ and IgG4-RKD− were compared. Twenty IgG4-RD patients who had definite etiology of renal impairment including diabetes, hypertension and etc. were excluded. Among the remained 450 IgG4-RD patients, 53 were diagnosed with IgG4-RKD+ . IgG4-RKD+ patients had older age at onset and at diagnosis. Male to female ratio of IgG4-RKD+ patients is significantly higher. In the IgG4-RKD+ group, the most commonly involved organs were salivary gland, lymph nodes and pancreas. It was found that renal function was impaired in approximately 40% of IgG4-RKD+ patients. The most common imaging finding is multiple, often bilateral, hypodense lesions. Male sex, more than three organs involved, and low serum C3 level were risk factors for IgG4-RKD+ in IgG4-RD patients. These findings indicate potential differences in pathogenesis of these two phenotypes.